2017
DOI: 10.21071/pbs.v0i4.5766
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating FIDO: Developing and pilot testing the Field Instantaneous Dog Observation tool

Abstract: HIGHLIGHTS• The Field Instantaneous Dog Observation (FIDO) tool, a non-invasive, field ready tool designed to capture the immediate welfare status of dogs housed in commercial breeding facilities was developed and pilot tested for inter-rater reliability.• Affiliative or neutral (green) responses to approach were most commonly identified by both novice and expert raters in this study.• Both expert and novice raters achieved substantial levels of agreement when using the behavioral component of the FIDO tool.• … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 30 publications
1
33
0
Order By: Relevance
“…Previous research on the welfare of dogs presumably from CBKs conducted using data originating from dog owner reports [ 9 ] has lacked empirical evidence from direct observations. However, with advances in the development of dog welfare assessment tools and increased direct access to commercial dog breeding premises [ 10 , 11 , 12 , 13 ], researchers are beginning to better understand the behavior and health status of this population and how to assess their overall welfare in a more holistic way. It is important for researchers, breeding facility operators, and inspectors to have access to highly functional, validated, and easy to use tools designed to measure canine welfare in the field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research on the welfare of dogs presumably from CBKs conducted using data originating from dog owner reports [ 9 ] has lacked empirical evidence from direct observations. However, with advances in the development of dog welfare assessment tools and increased direct access to commercial dog breeding premises [ 10 , 11 , 12 , 13 ], researchers are beginning to better understand the behavior and health status of this population and how to assess their overall welfare in a more holistic way. It is important for researchers, breeding facility operators, and inspectors to have access to highly functional, validated, and easy to use tools designed to measure canine welfare in the field.…”
Section: Introductionmentioning
confidence: 99%
“…It is important for researchers, breeding facility operators, and inspectors to have access to highly functional, validated, and easy to use tools designed to measure canine welfare in the field. For example, the development of the Field Instantaneous Dog Observation (FIDO) tool, which offers a means to assess the physical and behavioral welfare states of dogs in CBKs, including their physical and behavioral health, has played an important role in the move toward the collection of direct observational data from this population [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sourcing of dogs is an increasingly contentious issue. Concerns range from the quality of the conditions under which dogs are reared and bred [ 12 ], to the implications of acquisition methods for dog care and welfare. Although they only sampled the Chicago area, Freiwald et al (2014) found that how respondents acquired a dog was not an indicator of future willingness to spend money on veterinary care [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, one study assessing dogs' physical welfare and cleanliness in licensed commercial breeding facilities in Indiana found no significant problems in these areas (Hurt, 2016). In addition, Bauer et al (2017) found high proportions of affiliative behaviors in dogs in commercial breeding kennels. These inconsistencies give credence to the idea that with appropriate management, diligent commercial dog breeders may be able to meet dogs' welfare needs.…”
Section: Regulation Of Commercial Dog Breedersmentioning
confidence: 93%
“…This has culminated in fractious debates about how to meet the demand for companion dogs, while sustainably and ethically sourcing them. Commercial dog breeders currently help to supply US consumers with the purebred and 'designer' dogs they desire (Hurt et al, 2016;Bauer et al, 2017). In the US, dogs from such kennels are typically made available to consumers through sales in pet stores or via online retailers.…”
Section: Introductionmentioning
confidence: 99%